Recent trends of interventions in labor management at a tertiary care hospital - Thakkar, Nidhi D.; Agarwal, Sonali N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Aim of the study were to identify the changing trends in labor management in terms of rate of cesarean section (C-section), rate of trial of labor after C-section (TOLAC), rate of primary and repeat C-section, rate of episiotomy in primi and multi-gravida and percentage contribution of red cell concentrate (RCC) to total blood transfusion. Methods: The data was collected retrospectively for every year at SSG hospital, Baroda from 1st January 2014 to 31st December 2022. C-section rate was calculated per annum in percentage, which was again split into primary and repeat C-section rate. Leading indications for primary C-section were identified. Rate of total episiotomy, in primigravida and multigravida, trends of RCC transfusion rates and its contribution to total blood products were estimated. Appropriate statistical tests were applied to check level of significance. Results: C-section rate contributing to total confinements increased from 30.76% in 2014 to 37.6% in 2022, which was statistically significant. Contribution by primary C-section has decreased but repeat C-section has increased over these years. Common indications for primary C-section included fetal distress, MSL, breech presentation, non-progression of labor etc. Overall rate of episiotomy has increased from 41% in 2104 to 54.4% in 2022, with decrease in primigravida and increase in multigravida over these years but these rates are not significantly changed. Contribution of RCC to total transfusion significantly decreased from 76.1% in 2014 to 66% in 2022. Conclusions: Rate of total and for repeat C-section are increasing with time, so TOLAC and other strategies to reduce primary C-section should be focused upon. Episiotomy must not be routine and should be given when indicated only. Interventions to reduce requirement of blood transfusion must be strengthened. New oral and parenteral iron preparations should be accepted based on evidences.